Treatment adherence and quality of life of patients taking antihypertensive medications - Fitra Galih Nonasri; TA Larasati (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background: Hypertension as The Silent Killer characterized by blood pressure ≥140 mmHg/≥90 mmHg. Hypertensive people have lower quality of life compare to non-hypertensive people and they need an appropriate health behavior. Hypertensive medication without lifestyle modification and routine control of blood pressure increase cardiovascular complication even death that affecting quality of lifePurpose: To identify the characteristic and the dominant health behavior affecting quality of life among hypertensive farmer. Method: The minimum sample 103 hypertensive farmer ≥18 years old in Gunung Agung Village, Terusan Nunyai District, Central Lampung include in this cross sectional study after measuring the blood pressure. The data was taken by interviewing the participants using health seeking behavior questionnaire and Short Form-36, then multivariate analysis was performed using binary logistic regression.Results: A total of 103 hypertensive farmer dominant in the 1st grade of hypertension (63,2%), male (56,3%), 45-54 years old (35%), primary school as the last education background (45,6%), income rates ≤7 million/year (68%), and don’t take anti-hypertensive medications regularly (98,1%). Preventive and curative treatment as part of treatment efforts were the most dominant variable affecting quality of life (p=0,023; OR=0,096; CI=0,028-0,327).Conclusion: Quality of life of hypertension farmers was significantly related to attitude towards health (p=0.001; OR=0.218; CI=5.76-42.34), treatment effort (p=0.001; OR=1.86; CI=0.09-0 ,54), first time of treatment (p=0,001; OR=8,473; CI=3,10-23,17), and frequency of examination (p=0,023; OR=14,426; CI=5,81-40,16), where treatment efforts such as routine blood pressure control and taking anti-hypertensive drugs can improve quality of life (OR=4.208).